HUBUNGAN ANTARA DIABETES MELLITUS TIPE II DENGAN OSTEOARTHRITIS LUTUT PADA PASIEN DI RUMAH SAKIT UMUM AL - FAUZAN TAHUN 2016 - 2019 - Maruf Hari Subroto, (2019)
Osteoarthritis is a degenerative disease caused by joint cartilage damage. Research risk factors such as type 2 diabetes mellitus. The goal of this research is to identify the relation between type II diabetes mellitus and osteoarthritis of the knee. This research uses total sample of 45 patient taken with simple random sampling technique. The largest age group is 34 elderly people (75,6 %), the most gender groups is 34 women (75.6%), the most of HbA1c levels is non DM which is 30 people (66,7 %), the highest degree of severity of knee osteoarthritis is severe degree (4) as many as 28 people (62.2%). Statistical analysis using the Chi Square test with a p value > 0.05 showed no association between type II diabetes mellitus and knee osteoarthritis